2000
DOI: 10.1177/0044118x00032001002
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of the Troubles on the Young People's Psychological and Social Development and their School Life

Abstract: Throughout the history of the Troubles in Northern Ireland, concern has been expressed for the generations that have grown up against a backdrop of political violence. Despite the interest of local and international researchers in the psychological effects of the conflict on children's and adolescents' development, a firm understanding as to the psychological cost of the Troubles has not been reached. This fact largely can be attributed to the complex nature of the issue and the resultant methodological proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Evidence from Northern Ireland has shown that, during the ''Troubles'', those living in high violence areas reported more symptoms of physical illness than those living in areas of low violence (Cairns & Wilson, 1991). Muldoon, Trew, and Kilpatrick (2000) suggest that the consequences of the ''Troubles'' on young people's psychological well-being and social and school life are not clear. They also believe that problems tend to be associated with gender, poverty and deprivation, and these factors are associated with levels of community conflict.…”
Section: The Northern Ireland Contextmentioning
confidence: 99%
“…Evidence from Northern Ireland has shown that, during the ''Troubles'', those living in high violence areas reported more symptoms of physical illness than those living in areas of low violence (Cairns & Wilson, 1991). Muldoon, Trew, and Kilpatrick (2000) suggest that the consequences of the ''Troubles'' on young people's psychological well-being and social and school life are not clear. They also believe that problems tend to be associated with gender, poverty and deprivation, and these factors are associated with levels of community conflict.…”
Section: The Northern Ireland Contextmentioning
confidence: 99%
“…However, although there is some evidence that increased experience of the con¯ict may be related to acting out or externalising behaviour problems, this effect has only been observed in terms of psychometric pro® les and not in terms of the prevalence of antisocial behaviour. 22 There has been no comparative study of behaviour in schools between Northern Ireland and England and Wales to discover if indiscipline is less of a problem in Northern Ireland and therefore lower levels of exclusion could be expected. A survey of schools in Northern Ireland carried out by the Department of Education for Northern Ireland found that, for most schools, the behaviour of pupils is not a problem.…”
Section: Other Factors Impacting On School Exclusionsmentioning
confidence: 99%
“…At the same time, findings are inconsistent regarding the link between exposure to sectarian conflict and psychological symptoms within Northern Ireland (Muldoon, 2004; Muldoon, Trew, & Kilpatrick, 2000). Initial studies examining youth exposure to political violence and mental health in Northern Ireland suggested that youth living in segregated communities were highly traumatized (Fraser, 1974), and later studies suggested children remained resilient despite the assumed increased risk due to the prevalence of violence (Fee, 1980; Joseph, Cairns, & McCollam, 1993; McWhirter, 1983, as cited in Cairns, 1996).…”
Section: Introductionmentioning
confidence: 99%